Association between temperature rise from climate normal and sleep quality - Horim A. Hwang; Ayoung Kim; Jiwoo Park; Whanhee Lee; Hyun-Joo Bae; Sanghyuk Bae (Scientific Reports)
Abstract While there are numerous studies on the association between climate change and poor sleep quality, there are few studies on large population with a validated outcome measure that can portray a various aspects of poor sleep quality. A total of 211,159 participants from Korean Community Health survey 2018 were included to assess the impact of temperature rise on sleep quality. The primary independent variables are temperature average and temperature difference. Temperature average is yearly average temperature of each district, while temperature difference is the difference between yearly average temperature and climate normal derived from 1961 to 1990. The main outcome is overall sleep quality and sleep components measured by the Pittsburgh sleep quality index. Of the participants, 120,166 (81.48%) were dwelling in urban districts. Urban participants were more likely to report poor sleep quality per 1 °C increase in temperature difference (aOR 1.16 95% CI 1.05–1.29), while 1 °C increase in average temperature was not associated with poorer overall sleep quality. The temperature difference was also associated with shorter sleep duration, sleep fragmentation, bad dreams, too cold, cough or snore, and pain during sleep time. The increase in temperature compared to climate normal was associated with higher prevalence of poor sleep quality. More research on the climate change’s long-term impact on sleep quality is needed.